Strategic Initiative: A Business Plan for ASPIRE of Southwest Missouri - Frost, Andrew (Missouri Southern State University (Joplin, Mo.), 2013)
Summary: This research project details a business plan for ASPIRE of Southwest Missouri, including a new marketing strategy, an operational plan and a management plan. The project also describes the company's current financial position and its future contributions.; 1 online resource (30 pages) : illustrations, some colour, PDF file